LANGUAGE POLITENESS STRATEGY IN BUYING AND SELLING BASED ON GENDER - Mikha Joys; Binti Nurkhasanah; Sindy Alicia Gunawan (ELite Journal : International Journal of Education, Language, and Literature, 2022)
In buying and selling transactions process, sellers are required to provide the best service through polite speech to buyers. In that way, buyers will feel comfortable and valued with the services provided by the seller. Thus, this study purposes to explore the language politeness strategies contained in the speech between sellers and buyers by looking at the gender differences in Pasar Pagi, Bugis village, Samarinda. It focuses on the utterances delivered by sellers and buyers to find out how gender differences can affect politeness strategies in transactions in the market. This research employed a descriptive qualitative approach with recording and note-taking techniques for data collection. Meanwhile, Brown and Levinson’s theory is used to categorize data. The data are further analyzed in order to know the representation of language politeness strategies in speech acts in Pasar Pagi. Based on the analysis results, there are two language politeness strategies in the speech act of buying and selling at Pasar Pagi, namely bald on record and positive politeness. It can be said that sellers and buyers pay attention to language politeness strategies regardless of gender differences.